PENGARUH MEDIA PEMBELAJARAN CROSSWORD PUZZLE TERHADAP AKTIVITAS DAN HASIL BELAJAR BIOLOGI - Nurulfajri Nurulfajri (Cocos Bio, 2016)
This study aims to determine the effect of using Crossword Puzzle learning media on the activities and learning outcomes of biology in digestive system material to human class VIII MTs NW Rumbuk 2015/2016 academic year. This study uses experimental research. The study population was all eighth grade students of MTs NW Rumbuk in the 2015/2016 school year, a number of three classes. The research sample was determined randomly by cluster random sampling technique. One class experiment with crossword puzzle learning media and one control class using the lecture method. Data collection techniques using multiple choice tests consisting of 30 questions. Whereas to measure learning activities students use observation sheets. Analysis prerequisite test using normality, homogeneity and linearity test. The hypothesis test is with a manova test with a significant level of 5% with the help of IBM SPSS 22.Hypothesis test Fresults Ftable count, according to the data seen with the specified significance level is = 0.05 0.00 (~).Thus it can be concluded that there is an influence of the use of crossword puzzle learning media on biology learning activities and results